When Heidegger is a producer: being ecological according to version of Timothy Morton - A. G. Ivanov; I. N. Pupysheva (Омский научный вестник: Серия "Общество. История. Современность")
In the center of attention of the authors of the article is Timothy Morton’s book «Being Ecological». The book is devoted to the problems of ecological awareness and lifestyle. Morton’s unusual approach develops the ideas of Graham Harman, Immanuel Kant and Martin Heidegger, but does not offer any panacea in the era of mass extinction. Morton rather questions our own concern about finding this panacea. In an era when the ecological lifestyle seems heroic and sublime, he tells us: «you are already ecological». The authors are trying to trace how Morton develops the concepts of Kant and Heidegger, giving them, with the help of object-oriented ontology, a new and actual interpretation